2023
DOI: 10.1093/ije/dyad009
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effect of physical activity on cognitive function within the UK Biobank cohort

Abstract: Background Physical activity (PA) has been associated with benefits for cognitive function (CF), but previous estimates of the strength of this relationship may have been biased due to limitations in statistical modelling practices that are common among observational studies. We aimed to address this by using a rigorously constructed conceptual causal model to guide an empirical analysis estimating the effect of PA on CF in the UK Biobank cohort of middle-aged and older adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Participants gave informed consent and provided detailed demographic, socioeconomic, lifestyle and health-related data via a touchscreen questionnaire, including medication history. As previously described, participants then underwent a large range of physical and biological assessment measures, including repeated blood pressure measurements, height and weight, from which BMI was derived, accelerometery and neuroimaging visits 83,85 ; in addition to urine, saliva and blood collection for biomarker and genetic assessments as previous 84,86 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants gave informed consent and provided detailed demographic, socioeconomic, lifestyle and health-related data via a touchscreen questionnaire, including medication history. As previously described, participants then underwent a large range of physical and biological assessment measures, including repeated blood pressure measurements, height and weight, from which BMI was derived, accelerometery and neuroimaging visits 83,85 ; in addition to urine, saliva and blood collection for biomarker and genetic assessments as previous 84,86 .…”
Section: Methodsmentioning
confidence: 99%
“…These tests were developed specifically for UK Biobank, to enable computerized administration at scale without staff involvement, and are thus non-standardized. As previously described 85 , a battery of several baseline and follow-up cognitive tests were administered in English language to participants; covering four major cognitive domains (episodic and working memory, executive function, processing speed and attention).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, social factors like engagement in social activities, occupational history, and the presence of certain diseases have been found to play a role in cognitive function [9]. Moreover, physical activity has been recognized as a factor influencing cognitive function positively [10]. A Meta analysis conducted on preadolescent children, concluded that longitudinal physical activity programs have a positive effect on all cognitive domains, including executive function, memory, planning, attention, and academic performance [11].…”
Section: Introductionmentioning
confidence: 99%